Prevalence-Based Targets Underestimate Home Dialysis Program Activity and Requirements for Growth. Issue 3 (May 2018) - Bevilacqua, Micheli U.; Er, Lee; Copland, Michael A.; Singh, R. Suneet; Jamal, Abeed; Dunne, Órla Marie; Brumby, Catherine; Levin, Adeera
Background: Many renal programs have targets to increase home dialysis prevalence. Data from a large Canadian home dialysis pro gram were analyzed to determine if home dialysis prevalence accurately reflects program activity and whether prevalence-based assessments adequately reflect the work required for program growth. Methods: Data from home dialysis programs in British Columbia, Canada, were analyzed from 2005 to 2015. Prevalence data were com pared to dialysis activity data including intakes and exits to describe program turnover. Using current attrition rates, recruitment rates needed to increase home dialysis prevalence proportions were identified. Results: We analyzed 7, 746 patient-years of peritoneal dialysis (PD) and 1, 362 patient-years of home hemodialysis (HHD). The proportion of patients on home dialysis increased by 3.34% over the ten years examined, while the number of prevalent home dialysis patients increased 2.65% per year and the number of patients receiving home dialysis at any time in the year increased 4.04% per year. For every 1 patient net home dialysis growth, 13.6 new patients were recruited. Patient turnover included higher rates of transplantation in home dialysis than facility-based HD. Overall, the proportion dialyzing at home increased from 29.3 to 32.6%. Conclusions: There is high patient turnover in home dialysis such that program prevalence is an incomplete marker of total program activity. This turnover includes high rates of transplantation, which is a desirable interaction that affects home dialysis prevalence. The shortcomings of this commonly used metric are important for renal programs to consider, and better understanding of the activities that support home dialysis and the complex trajectories that home dialysis patients follow is needed